ANALISIS IMPLEMENTASI CHATBOT AI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA INDONESIA - Azmil Mukhibbatul Bariroh (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2025)
This article examines the use of AI-based chatbots in Islamic Religious Education (PAI) learning at the junior high school (SMP) level in Indonesia through a Systematic Literature Review of 30 selected studies. Chatbots are understood as AI programs capable of interacting with users through natural conversation. In the context of PAI learning, the main concepts of chatbots include interactivity, personalization, and sensitivity to religious values. Their implementation requires a multidimensional approach, such as strengthening digital infrastructure, training teachers and students through project-based models, providing accurate content that respects madhhab differences and local contexts, and applying humanistic pedagogy. Chatbots also support self-paced learning and facilitate personalized learning to improve learning outcomes.